Diseño de un sistema de monitoreo para la adquisición de señales electromiográficas no invasivas en extremidades superiores (2018)
The techniques and technologies to collect, analyze, represent and store medical data in a reliable way have evolved rapidly. One of these methodologies is the clinical surface electromyography, which allows recording and analyzing bioelectric activity useful for the diagnosis of congenital or acquired neuromuscular disorders, as well as determining the exact anatomic location of the problem and intensity. The electromyographic signal is a technique used for various applications in different areas such as neurology, rehabilitation, orthopedics, among others. This article presents the design of the stages of the development and implementation for the simulation of surface electromyographic (EMG) signals, by means of a non-invasive method, which provides the electrical activity of the muscles with great objectivity and promptness which are checked in upper limb muscles. For the implementation of the circuits, components of easy acquisition are used, contributing to the technological development of the country.